Rooted in Loss: Exploring Generational Trauma through a Postcolonial Lens in The Island of Missing Trees - Bashir, Saima; Ishaq, Muzamil (Annals of Human and Social Sciences, 2024)
The article explores Elif Shafak’s The Island of Missing Trees under the Delezuean notion of generational trauma. Ada, Kostas, and Defne try to figure out who they are while dealing with unfinished trauma and repressed memories. In their attempts to cope, forget, and move on from their traumatic experiences, they encouter collective trauma. The Deleuzean perspective is used to investigate how trauma affects people’s lives and is passed down from generation to generation. The study incorporates the idea of intergenerational transmission of memories to interpret how families with traumatic and violent historical events, in this case, the families who suffered during the intercommunal violence that destroyed Cyprus in 1974, pass their traumatic experiences from one generation to the other. However, generational pain can not only change the way one sees the world and oneself, but can also make new opportunities possible, thus making suffering lead to new ideas and creativity.